2016
DOI: 10.3174/ajnr.a4849
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Vulnerable Carotid Plaque

Abstract: BACKGROUND AND PURPOSE: MR imaging-detected carotid intraplaque hemorrhage indicates vulnerable plaque with high stroke risk. Angiotensin II stimulates intraplaque hemorrhage in animal models, and the angiotensin system is highly regulated by vitamin D. Our purpose was to determine whether low vitamin D levels predict carotid intraplaque hemorrhage in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…They used multivariable Poisson regression to determine a correlation between two carotid arteries and low Vitamin D levels. As the Vitamin D level increased, there was a significant decrease in the IPH volume in the carotid artery, with a p-value of 0.003, which is less than the alpha value of 0.05(McNally et al 2016). The figures show that Vitamin D decreases the IPH volume and the risk of cardiovascular disease and stroke since it is in the carotid artery.…”
mentioning
confidence: 76%
“…They used multivariable Poisson regression to determine a correlation between two carotid arteries and low Vitamin D levels. As the Vitamin D level increased, there was a significant decrease in the IPH volume in the carotid artery, with a p-value of 0.003, which is less than the alpha value of 0.05(McNally et al 2016). The figures show that Vitamin D decreases the IPH volume and the risk of cardiovascular disease and stroke since it is in the carotid artery.…”
mentioning
confidence: 76%
“…In contrast to the current results, Chen et al described the association of lower 25OHD levels and the presence of carotid plaques in Chinese type 2 diabetic patients [ 32 ]. Previous cross-sectional studies found an association between lower levels of 25OHD and cIMT [ 12 , 33 , 34 ]. In the large prospective Framingham Offspring Study, vitamin D deficiency was a predictor of cardiovascular disease only in subjects with hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…Animal models also indicate that IPH can be stimulated by angiotensin II administration. 102 In a human study, however, IPH was not associated with angiotensin II levels, but instead with low vitamin D. 103 Vitamin D is a known negative regulator of the angiotensin system and may have local effects on the vessel wall. 104 Although some have postulated that hypertension induces neovessel rupture and IPH, only a few studies have found a link between hypertension and IPH.…”
Section: Additional Markers Of Mri-detected Iphmentioning
confidence: 98%